The role of ultrasonography in the assessment of ulnar collateral ligament injury of the thumb – a diagnostic test accuracy meta-analysis. Issue 2 (1st April 2021) - Raheman, Firas J.; Rojoa, Djamila M.; Dhingra, Mohit; Siddiqui, Saad; Macdonald, Christopher R.
Abstract: The accurate diagnosis of ulnar collateral ligament (UCL) injuries of the thumb is important in identifying patients requiring surgery. Stener lesion, the most severe form of such injuries, is debilitating and leads to chronic instability if misdiagnosed. We evaluated the diagnostic accuracy of ultrasonography (USS) in UCL injuries. A systematic review of existing literature was performed with a meta-analysis using a bivariate mixed-effects model to estimate summary sensitivity and specificity. All observational studies were assessed, with participants of any age, who sustained UCL injuries of the thumb. A hierarchical model was used to generate a hierarchical summary receiver operating characteristic (HSROC) curves. We identified 17 studies reporting a total of 593 UCL injuries. Pooled estimates for sensitivity and specificity were 0.96 (95% CI 0.89–0.99) and 0.90 (95% CI 0.81–0.94), respectively for the diagnosis of Stener lesions; 0.81 (95% CI 0.66–0.93) and 0.87 (95% CI 0.67–0.96), respectively for non-displaced complete ruptures and 0.82 (95% CI 0.66–0.92) and 0.94 (95% CI 0.85–0.98), respectively for complete ruptures without Stener lesion. The area under the curve (AUC) for Stener diagnosis using USS was 0.98, suggesting excellent diagnostic accuracy. Our meta-analysis suggests that USS is a reliable and accurate method of diagnosis for UCL injuries. Moreover, it has excellent diagnostic accuracy for Stener lesions and may be used in the diagnostic work-up of UCL injuries with magnetic resonance imaging being reserved for ambiguous cases.